Population Pharmacokinetic-Based Model-Informed Precision Dosing: Current Implementation Status and Global Equity Gaps – A Structured Narrative Review - Aisyah, Novia Dani; Nugroho, S.Si., M.Si., Apt., Akhmad Kharis; Andayani, Tri Murti (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2026)
Background: Model-Informed Precision Dosing (MIPD) leverages population pharmacokinetics (PopPK) and Bayesian forecasting to optimise drug therapy in heterogeneous populations. Despite its theoretical promise, real-world implementation remains limited, particularly in low- and middle-income countries (LMICs). Objective: This review synthesises evidence on the clinical integration, outcomes, enablers, and barriers of population pharmacokinetic (PopPK)-based MIPD. Methods: A structured narrative review was conducted across five databases to identify studies reporting real-world PopPK implementation (2014-2025) in clinical settings. Results: Twenty-seven studies were included, predominantly from high-income countries (HICs). Antibiotics were the most studied drug class, particularly vancomycin, which dominated the therapeutic areas studied; however, routine clinical implementation remained minimal. MIPD improved pharmacokinetic target attainment, reduced ICU stay by 2.13 days, and generated cost savings of up to $12,324 per patient. Key enablers included clinician-pharmacist collaboration and user-friendly software, whereas barriers included inadequate therapeutic drug monitoring (TDM) infrastructure and digital disparities in LMICs. Conclusion: PopPK-based MIPD demonstrates clinical and economic benefits but faces significant global implementation challenges. Accessible software development, TDM infrastructure enhancement, and validation studies in underrepresented populations are essential.